Implications of Utilizing Protected Forest Areas for Geothermal Business: A Legal Analysis - Suyatna Suyatna; Ahmad Suryono; Ulil Amri; Rifky Leo Argadinata; Amara Diva Abigail (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Geothermal as an alternative and renewable energy is mostly located in the forest areas, including protected forests, where the use of forest areas for non-forestry activities is very selective and does not change the function of the forest itself. Geothermal and forestry regulations require synchronization regarding the use of protected forest areas so that they do not cause legal conflicts.Purpose/Objective Study: There are arose problems namely the existence of conflicting norms in regulating the use of protected forest areas for geothermal exploitation, between the Geothermal Law and the Forestry Law in combination with Government Regulation No. 24 of 2010 concerning the Use of Forest Areas and Regulation of the Minister of Environment and Forestry on Leasing of Forest Areas.Design/Methodology/Approach: This research method was normative research, using a statutory approach equipped with a comparative approach.Findings: The research finding was the setting of leasing forest areas for geothermal exploitation was contradictory and did not function to carry out the orders of the Forestry Law. The research implication is that the Government together with the Parliament must put into comprehensive special authorities and regulations related to the management and utilization of energy in forest areas so that there is no overlap and legal uncertainty in the use of forest areas.Paper Type: Research Article